AN ASSESSMENT OF EFFECTIVENESS IN PROSECUTION CRIMINAL JUSTICE ON THE ANTI-TRAFFICKING IN PERSONS ACT B.E. 2551 - Lerwongrat, Kittanathat (วารสารกระบวนการยุติธรรม, 2017)
This study used qualitative and quantitative research methods to evaluate the efficiency of justice departments in litigation according to the Anti-Trafficking Act B.E. 2551. This research employed documentary research, focus group meetings, and questionnaires. The quantitative sample group comprised of 100 persons selected using stratification sampling method, while the qualitative sample group comprised of 28 persons. The first focus group comprised of 30 persons and the second of focus group comprised of 35 persons which was specifically selected from justice personnel and related agencies. The study revealed that the Anti-Trafficking Act which has been enforced for 9 years and 3 amendments. The latest amendment of B.E. 2559 and Law Enforcement on May 25th, 2016 had changed from adversarial and accusatorial system to inquisitorial system in order to make the prevention and protection of human trafficking, as well as the jurisdiction more effective, quicker and fairer. It was also found that people were satisfied with the officers’ implementation of anti-trafficking act. The significant recommendations of the study are as follows: (1) The government should set an anti-trafficking policy as a national agenda. (2) The government must construct the Center for the Prevention and Suppression Human Trafficking in provinces for effective prosecution. (3) The government policy formulation must adopt a 5P approach as a guideline to prevent and suppress human trafficking.